2019
DOI: 10.1002/pon.5061
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in survivors of childhood brain tumour and the association of children's diseases on quality of their parents life

Abstract: Objective: Evaluation of children's quality of life (QoL) after finished brain tumour treatment and the association of children's diseases on quality of their parents' life.Methods: The study group was consisted of 46 children after brain tumour treatment (aged 4, 5, to 29 years old). The control group was composed of 104 students of primary, secondary, and high schools. One hundred fifty (104 + 46) parents were included in the study. Standardised QoL questionnaires (PEDsQL-4.0, WHOQOL-BREF) were used. Survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…A total of 14 studies are cross-sectional, 15 studies are longitudinal, and 1 study uses both longitudinal and cross-sectional data collection. Articles are included from the United States [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], Switzerland [ 30 , 31 , 32 , 33 ], South Korea [ 34 , 35 ], Canada [ 36 , 37 ], Japan [ 38 , 39 ], Netherlands [ 40 , 41 ], India [ 42 ], United Kingdom [ 43 , 44 ], Germany [ 45 ], Brazil [ 46 ], Italy [ 47 ], Poland [ 48 ], North American collaboration [ 49 ], European collaboration, [ 50 ] and an international collaborative [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 14 studies are cross-sectional, 15 studies are longitudinal, and 1 study uses both longitudinal and cross-sectional data collection. Articles are included from the United States [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], Switzerland [ 30 , 31 , 32 , 33 ], South Korea [ 34 , 35 ], Canada [ 36 , 37 ], Japan [ 38 , 39 ], Netherlands [ 40 , 41 ], India [ 42 ], United Kingdom [ 43 , 44 ], Germany [ 45 ], Brazil [ 46 ], Italy [ 47 ], Poland [ 48 ], North American collaboration [ 49 ], European collaboration, [ 50 ] and an international collaborative [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…No effect is observed between SES and HRQoL, however variable methods of determining SES are used, and there is low representation of families within the low SES categories. Five studies find no statistically significant differences by sex in patients who undergo RT [ 22 , 24 , 26 , 43 , 48 ]. Three studies find no correlation between age and HRQoL [ 22 , 24 , 43 ], while Musiol et al (2019) describe a weak negative correlation between age at diagnosis and self-reported emotional functioning [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Además, es un constructo multidimensional que está conformado por diferentes dimensiones, familia, trabajo, salud, etc. La vivencia del cáncer tiene importantes repercusiones sobre la satisfacción vital de los padres (16) . En este sentido, la calidad de vida de los padres de niños con cáncer se ve afectada de manera negativa por la enfermedad oncológica (17) .…”
Section: Introductionunclassified